2011
DOI: 10.1021/jp110455k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gold Nanoparticles in Liquid Polyethylene Glycol by Sputter Deposition and Temperature Effects on their Size and Shape

Abstract: Combining the use of liquid polyethylene glycol (PEG) as a capture medium with the sputter deposition technique, we developed the easy and simple preparation of gold nanoparticles (Au NPs) in liquid PEG with neither chemical reactions nor additional stabilizers. PEG was selected because of its ability to stabilize NPs and its environmental friendliness. We used PEG with an average molecular weight of 600 because it is in the liquid state at room temperature and has a vapor pressure low enough to endure the spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 46 publications
(96 reference statements)
5
111
1
Order By: Relevance
“…Hatakeyama et al used PEG with an average molecular weight of 600 as a sputtering medium, because it is in the liquid state at room temperature and has a vapor pressure low enough to endure the sputtering process [32]. The deposition was performed at a voltage of 1 kV, a current of 20 mA under an Ar pressure of [16][17][18][19] Pa, and at constant temperatures of 20, 30, 40, 50, and 60 o C. Although Au NPs were successfully synthesized in PEG, the size and size distribution of the Au NPs were larger and wider, than those of Au NPs in BMI-BF 4 , as illustrated in Fig.…”
Section: C-h-o-containing Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatakeyama et al used PEG with an average molecular weight of 600 as a sputtering medium, because it is in the liquid state at room temperature and has a vapor pressure low enough to endure the sputtering process [32]. The deposition was performed at a voltage of 1 kV, a current of 20 mA under an Ar pressure of [16][17][18][19] Pa, and at constant temperatures of 20, 30, 40, 50, and 60 o C. Although Au NPs were successfully synthesized in PEG, the size and size distribution of the Au NPs were larger and wider, than those of Au NPs in BMI-BF 4 , as illustrated in Fig.…”
Section: C-h-o-containing Polymersmentioning
confidence: 99%
“…First, metal NP synthesis using ionic liquids will be discussed, which includes the synthesis of single material NPs and the effect of sputtering conditions [19][20][21][22][23][24][25][26][27], various alloying strategies [15,23,24,28], and techniques for transferring synthesized NPs [29][30][31]. Subsequently, we discuss NP synthesis using low-volatile polymers, including the use of thiol compounds and transfer techniques [32][33][34][35][36][37][38][39]. Finally, potential applications of liquid medium sputtered NPs, such as their use as ORR electrocatalysts and Suzuki-Miyaura coupling reacScheme.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] The electronic contribution to the nonlinear refraction of these colloids were evaluated using the Z-scan technique with thermal management and the alloptical switching figures of merit for this composite system were also obtained. In addition, the third-order nonlinear susceptibility of AuNPs in an organic dispersant without the presence of other chemical impurities was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Since PEG does not have any functional groups stabilizing metal NPs, it has been reported that the viscosity affects the size of resultant NPs. 17 Thus, in the current work the amount of PEG was constant under different thiol concentrations. The thiol stabilizer used here was 11-mercaptoundecanoic acid (MUA).…”
mentioning
confidence: 96%
“…So far, several capturing matrices have been examined for the preparation of Au NPs by the matrix sputtering method and they can be categorized into (i) 6-mercaptohexyltrimethylammoniumbromide (6-MTAB) 15 and pentaerythritol tetrakis-(3-mercaptopropionate) (PEMP), 16 and (ii) propane-1,2,3-triol, 18 polyethylene glycol (PEG), 17,19,20 ionic liquids, 21,22 and pentaerythritol ethoxylate (PEEL). 16 Group (i) depends on the affinity of the mercapto group and can form very small (B1.3 nm) fluorescent Au NPs, while group (ii) depends mainly on the viscosity of themselves and forms rather large Au NPs (2-5 nm).…”
mentioning
confidence: 99%